MODERNISME PONDOK PESANTREN SEBAGAI INSTITUSI PENDIDIKAN ISLAM NON DIKOTOMIK - Faisal Kamal; Mukromin Mukromin (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
Islamic boarding schools (pesantren) are often perceived as educational institutions that only teach religious knowledge. In fact, this is not the case. Although this view is not entirely wrong either, because, in fact, this perception arises because of the character and characteristics of Islamic boarding schools (pesantren) which have been consistent in maintaining traditionalism values. Being inappropriate, when there is a view that corners Islamic boarding school institutions as institutions that are old-fashioned and anti-change, so they are considered to hamper the progress of education in Indonesia. This article focuses on the subject of Islamic boarding schools (pesantren)as an institution that is oriented towards a balance between religious and general knowledge. The findings in this paper are, (1) boarding schools(pesantren) are excellent educational institutions. He proved his superiority, structurally, institutionally, and culturally, that Islamic boarding schools are able to elaborate integrated Islamic education models as real manifestations in practicing non-dichotomous educational principles. (2) paradigmatically, culturally, in practice, that the perception of Islamic boarding schools (pesantren) as dichotomous Islamic educational institutions is indisputable. Because, Islamic boarding school (pesantren) is the only Islamic educational institution that is successful in realizing the benefits of modernism and the wisdom of traditionalism.